Historicizing Fear : Ignorance, Vilification, and Othering - Chunnu, Winsome M.; Boyce, Travis D. (Book collections on Project MUSE., 2019)
"A historical interrogation from a global perspective of the use of fear to vilify and persecute groups and individuals. Offering a look at racism, fearful framing, oppression, and marginalization, and how 'the Other' is defined and how fear is reinforced, spread, and used for political gain"--